KARAKTER ANTI-HERO SEBAGAI COUNTER-HEGEMONI SUPERHERO DALAM FILM DEADPOOL: ANALISIS COUNTER-HEGEMONI ANTONIO GRAMSCI - Muhammad Fathan Zamani; Abi Ihsanullah; Badri Badri (Universitas Aki, 2021)
Myth is an essential part in superhero roles. In modern superhero acts, a character may possess more than one myth. Thus, this portrayal is an ideal power to create supremacy. An author, even a director could employ the newly-created myth to overcome hegemonic power. As stated in Gramsci, there is an instrument to control, even surpass ideology. In the Deadpool 1 & 2 movie, the myth of superheroes is interpreted as the instrument of hegemony. The aims of this study are to find out what kind of superhero hegemony that will be countered in the Deadpool movie, what are the counter hegemony element in the Deadpool movie, and how are the Deadpool’s effort and his preparations doing ideological battle against the superhero existence. This research uses hegemony and counter-hegemony theory according to Antonio Gramsci. This research applies descriptive qualitative method. The findings are Deadpool’s act of violence and his merc-with-mouth assuming his role as an anti-hero. However, Deadpool finally encountered the existing myth of superheroes ideologically. Unexpectedly, Deadpool offers a solution to the existing hegemony.